Exploring the Influence of Ethical Consumption on Sustainable Fashion Choices in Saudi Arabia - Muhammad, Sally Majid Thabet; Al-Dabbagh, Maha Abdullah (Journal of Humanities & Social Sciences, 2023)
Ethical fashion consumers are essential for growing the ethical fashion sector as their purchasing decisions and experiences are influenced by ethical concerns. Reducing excess packaging and materials is where ethical consumerism and business ethics intersect. Examining factors that affect ethical procurement behaviour and the interpretation of ethical consumption can provide insight into how to promote sustainability in the fashion industry.This study aims to identify the concept of ethical consumption of sustainable fashion to achieve sustainability in Saudi Arabia's fashion industry. It also evaluates the potential to raise Saudi consumers' awareness of sustainable fashion. This aligns with Saudi Vision 2030's goal of building a sustainable economy. Introducing the concept of sustainability in fashion and its importance to the environment can increase society's awareness of ethical consumption and sustainable fashion and its impact on purchasing behaviours.Using an analytical descriptive approach, the study surveyed 259 Saudi consumers. The results found that many respondents lack comprehensive knowledge of ethical consumption and sustainable fashion, indicating a need for educational initiatives. Despite limited understanding, respondents' religious ethics influence their purchase decisions, demonstrating a tendency toward environmentally conscious purchases.To ensure effectiveness, the study recommends creating educational programs and awareness campaigns about sustainable fashion and ethical consumption tailored to Saudi Arabia's cultural and religious context. This could help improve consumers' knowledge while leveraging their existing ethical values to promote more sustainable purchasing behaviours.
Keywords: Ethical consumption; consumer behavior; sustainable fashion